Racial Variation in Serum Lipid and Lipoprotein Levels in Type 2 Diabetic Subjects of Bangladesh - Hoque, Mohammad Razuanul; Kabir, Md Golam; Sikdar, Dwaipayan (Journal of Bio-Science, 2011)
Context: Racial and sex differences are documented globally regarding patterns of serum lipids among diabetic patients. Differences of lipid profile of normal and diabetic subjects of the different ethnic groups of Bangladesh may differ. Objectives: To find out if there were any differences in the serum lipid and lipoprotein levels in the type 2 diabetic patients of two different races namely, Bangalee and Chakma of Bangladesh. Materials and Methods: Study population consisted of 76 (Chakma / Bangalee: 35 / 41) patients aged between 40-60 years with type 2 diabetes mellitus who were on follow-up at the Rangamati Diabetes Hospital, Chittagong Hill Tract, Bangladesh and forty (Chakma / Bangalee: 20 / 20) non-diabetic subjects of same age were randomly selected as control. Biochemical parameters analyzed include - Serum total cholesterol and triglyceride (TG), serum high-density lipoprotein (HDL), low-density lipoprotein (LDL) cholesterol and atherogenic index. Results: Dyslipidemia was found in the diabetic patients of both races and the patients had higher serum TG), atherogenic index and lower serum HDL than their normal counterpart. The Bangalee patients were found to have higher TG and lower atherogenic index compared with the Chakma patients although no racial differences found regarding total, HDL and LDL cholesterol. Also no differences were found between the lipid profiles of normal control subjects of these two races. Conclusion: Present study confirms that racial differences exist in serum lipid abnormalities between Chakma and Bangalee subjects with type 2 diabetes. Key words: Diabetes Type 2; Triglyceride; Lipoprotein; Total cholesterol; Bangalee; Chakma. DOI: 10.3329/jbs.v17i0.7116 J. bio-sci. 17: 113-116, 2009